Are mass-media campaigns effective in preventing drug use? A Cochrane systematic review and meta-analysis. Issue 9 (3rd September 2015) - Allara, Elias; Ferri, Marica; Bo, Alessandra; Gasparrini, Antonio; Faggiano, Fabrizio
Abstract : Objective: To determine whether there is evidence that mass-media campaigns can be effective in reducing illicit drug consumption and the intent to consume. Design: Systematic review of randomised and non-randomised studies. Methods: We searched four electronic databases (MEDLINE, EMBASE, ProQuest Dissertations & Theses A&I and CENTRAL) and further explored seven additional resources to obtain both published and unpublished materials. We appraised the quality of included studies using standardised tools. We carried out meta-analyses of randomised controlled trials and a pooled analysis of interrupted time-series and controlled before-and-after studies. Results: We identified 19 studies comprising 184 811 participants. Pooled analyses and narrative synthesis provided mixed evidence of effectiveness. Eight interventions evaluated with randomised controlled trials leaned towards no evidence of an effect, both on drug use (standardised mean difference (SMD) −0.02; 95% CI −0.15 to 0.12) and the intention to use drugs (SMD −0.07; 95% CI −0.19 to 0.04). Four campaigns provided some evidence of beneficial effects in preventing drug use and two interventions provided evidence of iatrogenic effects. Conclusions: Studies were considerably heterogeneous in type of mass-media intervention, outcome measures, underlying theory, comparison groups and design. Such factors can contribute to explaining the observed variability in results. Owing to the risk of adverse effects, caution is needed in disseminating mass-media campaigns tackling drug use. Large studies conducted with appropriate methodology are warranted to consolidate the evidence base.